Two hybrid plasmids with Drosophila melanogaster. DNA sequences complementary to mRNA coding for the major heat shock protein. - Schedl, P.; Artavanis-Tsakonas, S.; Steward, R.; Gehring, W.J.; Mirault, M.E.; Goldschmidt-Clermont, M.; Moran, L.; Tissieres, J. (Cell, 1978)
The isolation and partial characterization of two cloned segments of Drosophila melanogaster DNA containing "heat shock" gene sequences is described. We have inserted sheared embryonic D. melanogaster DNA by the poly(dA-dt) connector method (Lobban and Kaiser, 1973) into the R1 restriction site of the ampicillin-resistant plasmid pSF2124 (So, Gill and Falkow, 1975). A collection of independent hybrid plasmids was screened by colony hybridization (Grunstein and Hogness, 1975) for sequences complementary to in vitro labeled polysomal poly(A)+ heat shock RNA. Two clones were identified which contain sequences complementary to a heat shock mRNA species that directs the in vitro synthesis of the 70,000 dalton heat-induced polypeptide. Both cloned segments hybridize in situ to the heat-induced puff sites located at 87A and 87C of the salivary gland polytene chromosomes.